A typology of education and training provisions for low educated adults: categories and definitions. Issue 1 (2nd January 2018) - Boeren, Ellen; Whittaker, Susan
Abstract: It is Europe's ambition to be a strong knowledge based economy. The European Commission recognises the role of lifelong learning in achieving this aim. However, exploring participation rates in post-compulsory learning, it is clear that access to education and training is unequally distributed in society. We know that participation rates vary by socio-economic and socio-demographic groups, as well as by country. However, the role of education and training institutions in facilitating and enabling participation is less well known and deserves further in-depth attention. In order to fill this gap, we scrutinised definitions and categorisations of adult education provisions as published by the leading international organisations in the field of education and training. We paid specific attention to opportunities available for the lowest educated adults in society. Based on our review, we constructed a new typology consisting of seven categories for addition to the knowledge base and use in our own Horizon 2020 project. The categories are: (1) basic skills and basic education, (2) second chance education at upper secondary levels, (3) post-secondary VET, (4) apprenticeships, (5) training that forms part of Active Labour Market Policies, (6) workplace or job-related learning and (7) personal or social learning.